Transcriptome Analysis Identified Genes for Growth and Omega-3/-6 Ratio in Saline Tilapia - Lin, Grace; Thevasagayam, Natascha M.; Wan, Z. Y.; Ye, B. Q.; Yue, Gen Hua (Frontiers in Genetics, 2019)
Growth and omega-3/-6 ratio are important traits in aquaculture. The mechanisms underlying quick growth and high omega-3/-6 ratio in fish are not fully understood. The consumption of the meat of tilapia suffers a bad reputation due to its low omega-3/-6 ratio. To facilitate the improvement of these traits and to understand more about the mechanisms underlying quick growth and high omega-3/-6 ratio, we conducted transcriptome analysis in the muscle and liver of fast- and slow-growing hybrid saline tilapia generated by crossing Mozambique tilapia and red tilapia. A transcriptome with an average length of 963 bp was generated by using 486.65 million clean 100 bp paired-end reads. A total of 42,699 annotated unique sequences with an average length of 3.4 kb were obtained. Differentially expressed genes (DEGs) in the muscle and liver were identified between fast- and slow-growing tilapia. Pathway analysis classified these genes into many pathways. Ten genes, including foxK1, sparc, smad3, usp38, crot, fadps, sqlea, cyp7b1, impa1 and gss, from the DEGs were located within QTL for growth and omega-3, which were previously detected content in tilapia, suggesting that these ten genes could be important candidate genes for growth and omega-3 fatty acid content. Analysis of SNPs in introns 1 and 2 of foxK1 revealed that the SNPs were significantly associated with growth and omga-3/-6 ratio. This study lays the groundwork for further investigation of the molecular mechanisms underlying the phenotypic variation of these two traits and provides SNPs for selecting these traits at fingerling stage.